95.3k views
4 votes
Solve. 10x^2 = 6 + 9x10x 2 =6+9x10, x, start superscript, 2, end superscript, equals, 6, plus, 9, x Choose 1 answer: Choose 1 answer: (Choice A) A x =\dfrac{5 \pm \sqrt{65}}{-2}x= ?2 5± 65 ? ? x, equals, start fraction, 5, plus minus, square root of, 65, end square root, divided by, minus, 2, end fraction (Choice B) B x =\dfrac{9 \pm \sqrt{321}}{20}x= 20 9± 321 ? ? x, equals, start fraction, 9, plus minus, square root of, 321, end square root, divided by, 20, end fraction (Choice C) C x =\dfrac{4 \pm \sqrt{26}}{10}x= 10 4± 26 ? ? x, equals, start fraction, 4, plus minus, square root of, 26, end square root, divided by, 10, end fraction (Choice D) D x =\dfrac{-1 \pm \sqrt{109}}{18}x= 18 ?1± 109 ? ?

User Clawoo
by
5.2k points

2 Answers

7 votes

Answer:

B

Explanation:

I got it right

User Shadoweb
by
5.0k points
5 votes

Answer:

Option B.

Explanation:

If a quadratic equation is defined as


ax^2+bx+c=0 .... (1)

then the quadratic formula is


x=(-b\pm √(b^2-4ac))/(2a)

The given equation is


10x^2=6+9x

It can rewritten as


10x^2-9x-6=0 .... (2)

On comparing (1) and (2) we get


a=10,b=-9,c=-6

Using quadratic formula we get


x=(-(-9)\pm √((-9)^2-4(10)(-6)))/(2(10))


x=(9\pm √(81+240))/(20)


x=(9\pm √(321))/(20)

Therefore, the correct option is B.

User Craig McGuff
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.